In silico and computational analysis of zinc finger motif-associated homeodomain (ZF-HD) family genes in chilli (Capsicum annuum L) - Islam, Md. Abir Ul; Nupur, Juthy Abedin; Shafiq, Muhammad; Ali, Qurban; Sami, Adnan; Shahid, Muhammad Adnan (BMC genomics, 2023)
Zinc finger-homeodomain (ZHD) proteins are mostly expressed in plants and are involved in proper growth and development and minimizing biotic and abiotic stress. A recent study identified and characterized the ZHD gene family in chilli ( Capsicum annuum L.) to determine their probable molecular function. ZHD genes with various physicochemical characteristics were discovered on twelve chromosomes in chilli. We separated ZHD proteins into two major groups using sequence alignment and phylogenetic analysis. These groups differ in gene structure, motif distribution, and a conserved ZHD and micro-zinc finger ZF domain. The majority of the CaZHDs genes are preserved, early duplication occurred recently, and significant pure selection took place throughout evolution, according to evolutionary study. According to expression profiling, the genes were found to be equally expressed in tissues above the ground, contribute to plant growth and development and provide tolerance to biotic and abiotic stress. This in silico analysis, taken as a whole, hypothesized that these genes perform distinct roles in molecular and phytohormone signaling processes, which may serve as a foundation for subsequent research into the roles of these genes in other crops.